Bhutan Gender Policy Note - World Bank Group (Washington, DC, 2014)
Bhutan has undergone a major socio-economic transformation over the past few decades. Today, as a middle-income country guided by the unique development philosophy of Gross National Happiness, it continues to develop rapidly and become more integrated into the global economy. Coinciding with its development, Bhutan has also made considerable strides in closing gaps in gender equality. The analysis of the Gender Policy Note (GPN) focuses on specific issues related to economic empowerment. It analyzes patterns related to specific aspects of the economic empowerment of both men and women by applying the analytical framework of the 2012 World Development Report on Gender and Development to the Bhutan context. For the areas of focus, the report examines overall indicators on gender and identifies areas where gender gaps persist: agricultural land holding and inheritance practices, and gender gaps in labor markets and job quality. In Bhutan, most women acquire land ownership through inheritance, particularly in matrilineal communities. Unlike in other countries, the matrilineal inheritance practice offers economic opportunities for Bhutanese women and contributes to their relatively equal status with men. In addition, land holding through inheritance can also affect economic choices, particularly the decision to remain in one's village. Bhutan has made tremendous progress in female labor force participation, but the quality of jobs for women is still an issue. Although women's participation in the labor force has increased, it has not translated into improvements in employment quality. The Labor Force Survey shows that Bhutanese women work in lower quality jobs than men-women who earn income from work outside the home; their earnings are only 75 percent of men's earnings. The report recommends policy interventions in five main areas: first, it promotes equal ownership and agency over land. The policy appears to be working well in most areas of the country, and families are moving toward equal inheritance. Second, women's economic endowment could be augmented to increase labor productivity and earnings. Third, child care, along with vocational and life-skills training tailored for girls could women's access to good jobs. Fourth, social norms that lead to gender inequality could be addressed by promoting a greater role for men as fathers and caregivers and men's participation in housework. Finally, the report recognizes the need to conduct further research to better understand the gender gap in happiness.